Regional Lymph Node Involvement Is Associated With Poorer Survivorship in Patients With Chondrosarcoma: A SEER Analysis. Issue 11 (November 2019) - Wan, Lu; Tu, Chao; Li, Shuangqing; Li, Zhihong
Abstract: Background: Regional lymph node involvement is thought to be rare in patients with chondrosarcoma, but its actual prevalence is unclear. Additionally, it is often not considered when prognostic factors are analyzed in patients with chondrosarcoma. However, it has been well established that lymph node involvement is a poor prognostic marker in patients with many types of bone and soft tissue sarcoma, including rhabdomyosarcoma, osteosarcoma, and Ewing's sarcoma. Although lymph node metastases are rare among all sarcoma types, it is important to consider whether lymph node metastases should be assessed in patients with chondrosarcoma because these metastases may impact survival. Questions/purposes: (1) What is the reported prevalence of regional lymph node involvement in patients with chondrosarcoma? (2) Do patients who have chondrosarcomas with regional lymph node involvement have different clinicopathologic presentations and survival than patients without regional lymph node involvement? (3) Is regional lymph node involvement independently associated with prognosis in patients with chondrosarcoma? Methods: The data of patients with chondrosarcoma registered in the Surveillance Epidemiology and End Results database (SEER) (1988-2015) were analyzed for the reported prevalence of regional lymph node involvement and its relationship with clinicopathologic features and the 5-year overall survival rate. From 1988 to 2015, 5528 patients with chondrosarcoma were registered in the SEER database. After screening by the inclusion criterion—chondrosarcoma as the first primary tumor, diagnosis with histology confirmation, patients with active followup and available information about regional node status—3374 patients met the inclusion criteria and were analyzed. Demographics and clinicopathologic data were compared using chi-square or Fisher's exact tests. Logistic regression analysis was used to assess the adjusted odds ratio. The overall survival rate was estimated with Kaplan-Meier curves and log-rank tests. Univariate and multivariate analyses of overall survival were performed with Cox proportional hazard models. In addition, a series of sensitivity analyses were performed to assess the robustness of the final Cox proportional hazard model. Results: Forty-four patients (1.3%) were recorded in the database as having regional lymph node involvement at the time of the primary diagnosis. Lymph node metastases were more likely to be reported in an extraskeletal primary site (3% [13 of 426] versus 1% [31 of 2948], adjusted odds ratio [OR] = 2.9, 95% CI, 1.5–5.8; p = 0.003) for bone primary sites and tumors with maximum diameter ≥ 8 cm (2% [26 of 1045] versus 1% [10 of 1075], adjusted OR = 2.9, 95% CI, 1.3–6.3; p = 0.008) and poorer differentiation (4% [24 of 608] versus 1% [14 of 2308], adjusted OR = 4.0, 95% CI, 2.0–8.2; p < 0.001), and in those with distant metastases (7% [14 of 203] versus 1% [30 of 3148], adjusted OR = 3.5, 95% CI, 1.7–7.1, p = 0.001). The 5-year overall survival rates of patients with and without regional lymph node involvement were 28% (95% CI, 15–42%) and 77% (95% CI, 75–78%), respectively (p < 0.001). After controlling for age, sex, race, grade, metastatic status, size, and histologic subtype, the presence of regional lymph node involvement was associated with poorer survival (hazard ratio, 2.20; 95% CI, 1.50–3.24; p < 0.001); this finding was confirmed in several sensitivity analyses. Conclusion: The prevalence of regional lymph node involvement in patients with chondrosarcoma was 1.3% in the SEER database. Although chondrosarcomas are rare, patients with chondrosarcomas who have regional node metastases have a poorer prognosis than those who have not reported to have them. This may underrepresent the true proportion of patients with lymph node metastases given the inaccuracies of reporting in this database, but we believe these findings indicate that clinicians should examine patients more carefully for chondrosarcoma with lymph node metastases. Future studies are needed to assess potential treatment strategies to improve the prognosis of these patients. Level of Evidence: Level III, prognostic study.